Digitalization of Tobacco Taxation in Bangladesh: Reducing Evasion and Enhancing Public Health - Shah, AMM Mubassher (Journal of Information System and Informatics, 2025)
This study investigates the worldwide practice of digital tax systems to develop a digital taxation model for Bangladesh and identifies the prospects and challenges of implementing this model to address tax evasion. This study applies a qualitative approach to research. 30 in-depth interviews (IDI) with retailers of tobacco products and 10 key informant interviews (KII) with National Board of Revenue (NBR) officials, Tobacco control activists, and tax experts have been conducted using semi-structured interview guidelines. Secondary data has been collected from various reports, and journal articles. Data has been analyzed using the thematic analysis technique. The potential benefits of implementing a digitalized tax system encompass minimization of tax evasion, better monitoring, tracking, and tracing systems, transparent tax administration, and developing an efficient tax collection system. Despite the many advantages of digital tax systems, several challenges must be addressed. These include administrative resistance due to a lack of skilled manpower and modern infrastructure and the difficulties associated with registering tobacco companies and farmers. The implementation of proposed digital taxation model is expected to control tobacco tax evasion which ultimately increases prices and contributes to the overall goal of reducing tobacco consumption and enhance public health in Bangladesh.